THE INFLUENCE OF CONSUMER BEHAVIOR AND PRODUCT QUALITY ON PURCHASING DECISIONS IN PANDAN ROTI RAOS, SUKABUMI REGENCY, INDONESIA - SINDI KRISNANDARI; ISMARTAYA; ENDANG SILANINGSIH (CV KULTURA DIGITAL MEDIA, 2023)
This study ains to determine the effect of consumer behavior and product quality on purchasing decisions on Roti Raos Pandan in Sukabumi Regency. Sampling amounted to 66 respondents. A quantitative methode is used in this research. Data collection techniques through questionnaires, abservations dan interview. An instrument test is used for data analysis, consisting of validity test, a reliability test, and classical assumption test as well as descriptive analysis for multiple linear regression and hypothesis testing. The results showed that consumer responses to consumer behavior were categorized as good. consumer responses to product quality are categorized as good. Consumer resnposes to purchasing decision on Roti Raos Pandan are categorized as interested. Simultaneously and partially, consumer behavior and product quality have a positive and significant effect on purcashing decisions on Roti Raos Pandan in Sukabumi Regency.